ABSENSI ONLINE BERBASIS ANDROID (IMPLEMENTASI PLATFORM APPSHEET) - Patresia, Putri; Wali, Muhammad; Imilda (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2022)
This study aims to discuss online attendance using an android designed with an appsheet and spreadsheet which will make it easier for teachers to process attendance at school, the results of this research are applications that utilize the QR Code as the main component in assisting the attendance process for each teacher. The results of research with the application of QR Code technology made using AppSheet in the attendance system for teachers of the Kuta Pasie Public Elementary School, Baitussalam District, Aceh Besar Regency with an Android device can speed up the attendance process, besides that they can record attendance accurately and quickly. In the results of the trial system that has been completed and successfully created, the system will soon be implemented on an Android smartphone.